PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. BANK CENTRAL ASIA. TBK CABANG SURYOPRANOTO - Darmeinis; Nella Citra Ayu (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
This study aims to measure the extent to which the level of service quality on the level of customer satisfaction of PT Bank Central Asia Tbk. Suryopranoto Branch. This research uses descriptive quantitative analysis methodology with correlation analysis, determination analysis, and regression analysis. This study has 40 (forty) respondents consisting of men and women. The data used are quantitative data obtained from questionnaires distributed to respondents from PT. BANK BCA Tbk. KCU Suryopranoto Jl. Suryopranoto, Central Jakarta. The results of this study indicate that from that customer satisfaction (X) increases positively and is influenced by service, if there is no (x = o), then the level of satisfaction increases positively. There is a very strong relationship between service and customer satisfaction 79.21%, meaning the other factors are 20.79%.